Evaluation of Accounting Treatment for Fixed Asset According to PSAK No.16 at PT Pos Indonesia (Persero) Pontianak - B1031141033, PAULINUS RIONALDO PUDA BAKTI B1031141033 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
This research presented the accounting treatment for fixed assets of PT Pos Indonesia (Pontianak branch), the company is a service company. The purpose of this study is to determine whether the accounting treatment of the fixed assets of PT Pos Indonesia (Pontianak branch) was in accordance with PSAK No. 16 and to find out the constraints in the application of PSAK No.16.The discussions in this research are about how PT Pos Indonesia (Pontianak branch) determining the acquisition, acquisition price, and expenditure during the use of fixed assets, as well as the determination of depreciation and presentation of fixed assets on the balance sheet, whether it is in accordance with predetermined financial accounting standards. In the writing of this study, the author used a case study method by obtaining facts about the policy of accounting for fixed assets through interviews, observation, and documentation. From the research that has been carried out, the author obtain the results of this research is that the company policy in accounting treatment for fixed assets are in accordance with PSAK No. 16.Â Keywords: Fixed Assets, Application of Accounting for Fixed Assets, Recognition of Fixed Assets, Depreciation of Fixed Assets, PSAK No. 16.Â